Lanthanum slag treatment method
Through the combination method of lanthanum slag pre-calcination and smelting raw materials, the problems of low rare earth recovery rate and large amount of smelting solid waste slag in rare earth ferrosilicon production are solved, and high purity and high recovery rate of rare earth ferrosilicon alloy production are achieved.
Patent Information
- Application Number
- CN202510118052.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-24
- Publication Date
- 2025-03-28
AI Technical Summary
The existing rare earth ferrosilicon alloy production methods have problems such as low rare earth element recovery rate, large amount of smelting solid waste slag, and high residual rare earth content in smelting slag.
By combining lanthanum slag pre-calcination and smelting raw materials, rare earth ferrosilicon alloy is formed by pre-calcination of lanthanum slag at 400-600°C and smelting with carbonaceous reducing agent and silica at 1700-2200°C.
The rare earth recovery rate is improved, the amount of smelting solid waste slag is reduced, and the purity of rare earth ferrosilicon alloy is improved.
Abstract
Description
Technical Field
[0001] The invention relates to a method for treating lanthanum slag. Background Art
[0002] Lanthanum slag is the solid waste left after the lanthanum thermal reduction method is used to prepare rare earth metals. It contains a large amount of rare earth elements. If the rare earth elements in the lanthanum slag can be reused, it will greatly reduce costs and make full use of rare earth resources.
[0003] Rare earth ferrosilicon alloys are widely used in metallurgy, casting, machinery, military and other fields. The main production methods of rare earth ferrosilicon alloys are silicon thermal reduction, carbon thermal reduction, molten salt electrolysis and melting method. Silicon thermal reduction and carbon thermal reduction have become the mainstream methods of large-scale industrial production due to their high production efficiency and large production volume. In the silicon thermal reduction method, ferrosilicon is first smelted in an electric furnace, and then ferrosilicon is used as a raw material to add rare earth materials and calcium oxide for smelting to obtain rare earth ferrosilicon alloys. This process has the disadvantages of low rare earth element recovery rate, large amount of smelting solid waste slag, and high residual rare earth content in smelting slag. The carbon thermal reduction method uses rare earth concentrate, silica and carbonaceous reducing agent as raw materials to continuously smelt rare earth ferrosilicon alloys in a submerged arc furnace. The raw material cost of the carbon thermal reduction method is relatively low, but it is easy to form high melting point rare earth carbides during the smelting process. Rare earth carbides gather at the bottom of the furnace to form furnace nodules, causing the bottom of the furnace to rise rapidly and the furnace condition is difficult to stabilize. In addition, the stability of the carbon thermal reduction method is poor. Summary of the invention
[0004] The object of the present invention is to provide a method for treating lanthanum slag, which can transform solid waste lanthanum slag into rare earth ferrosilicon alloy. Furthermore, the purity of the rare earth ferrosilicon alloy obtained by the treatment method of the present invention is high. Furthermore, the treatment method of the present invention has a high rare earth recovery rate.
[0005] The above purpose is achieved through the following technical solutions.
[0006] The present invention provides a method for treating lanthanum slag, comprising the following steps:
[0007] (1) pre-baking a green body containing a first carbonaceous reducing agent and lanthanum slag at 400 to 600° C. for 50 to 120 minutes to obtain a pre-baked product;
[0008] (2) smelting the smelting raw materials including the pre-baked product, the second carbonaceous reducing agent and silica at 1700-2200° C. for 3-8 hours to obtain an alloy melt;
[0009] (3) Casting the alloy melt to obtain rare earth ferrosilicon alloy.
[0010] The first carbonaceous reducing agent is selected from one or more of coke, blue charcoal, semi-coke, charcoal, gas coke, bituminous coal, and petroleum coke. Preferably, the first carbonaceous reducing agent is blue charcoal.
[0011] The amount of the first carbonaceous reducing agent used is 20-30wt% of the theoretical amount of rare earth oxides contained in the reduced silica and lanthanum slag, based on the fixed carbon contained in the first carbonaceous reducing agent. Preferably, it is 23-27wt% of the theoretical amount of rare earth oxides contained in the reduced silica and lanthanum slag. This helps to reduce the impurity content of the product and improve the rare earth recovery rate.
[0012] Preferably, the pre-calcination temperature is 450-500° C. This helps to reduce the impurity content of the product and improve the rare earth recovery rate.
[0013] Preferably, the pre-calcination time is 50 to 80 minutes, which helps to reduce the impurity content of the product and improve the rare earth recovery rate.
[0014] The amount of lanthanum slag used can be determined according to the resulting rare earth ferrosilicon alloy product.
[0015] The second carbonaceous reducing agent is selected from one or more of coke, blue charcoal, semi-coke, charcoal, gas coke, bituminous coal, and petroleum coke. Preferably, the second carbonaceous reducing agent is blue charcoal. The second carbonaceous reducing agent may be the same as the first carbonaceous reducing agent, or may be different from the first carbonaceous reducing agent; preferably, the second carbonaceous reducing agent is the same as the first carbonaceous reducing agent.
[0016] The amount of the second carbonaceous reducing agent used is 100-180 wt% of the theoretical amount of rare earth oxides contained in the reduced silica and lanthanum slag, preferably 120-150 wt%, which helps to reduce the impurity content of the product and improve the rare earth recovery rate.
[0017] Preferably, the smelting temperature is 1800-2000° C. The smelting can be carried out in a submerged arc furnace. The smelting temperature may refer to the furnace bottom temperature of the submerged arc furnace. This helps to reduce the impurity content of the product and improve the rare earth recovery rate.
[0018] Preferably, the smelting time is 4 to 6 hours, which helps to reduce the impurity content of the product and improve the rare earth recovery rate.
[0019] In certain embodiments, the smelting feedstock consists of a pre-calcined product, a second carbonaceous reductant, and silica.
[0020] According to the treatment method of the present invention, preferably, the average particle size of the lanthanum slag is 5-30 mm, the average particle size of the first carbonaceous reducing agent is 5-30 mm, the average particle size of the second carbonaceous reducing agent is 5-30 mm, the average particle size of the silica is 40-150 mm, and the diameter of the minimum enclosing sphere of the blank is 100-300 mm.
[0021] More preferably, the average particle size of the lanthanum slag is 15 to 25 mm.
[0022] More preferably, the average particle size of the first carbonaceous reducing agent is 15 to 25 mm.
[0023] More preferably, the average particle size of the second carbonaceous reducing agent is 15 to 25 mm.
[0024] More preferably, the diameter of the smallest surrounding sphere of the blank is 150-250 mm.
[0025] In some embodiments, the blank is a cylinder. The diameter of the bottom surface of the blank may be 100-300 mm, preferably 150-250 mm. The height of the blank may be 100-300 mm, preferably 150-250 mm.
[0026] More preferably, the average particle size of the silica is 80 to 120 mm.
[0027] Controlling the particle size of the raw materials within the above range is helpful for sufficient reaction between the raw materials.
[0028] According to the treatment method of the present invention, preferably, the content of fixed carbon in the first carbonaceous reducing agent is greater than or equal to 80wt%, and the ash content is less than or equal to 10wt%;
[0029] The second carbonaceous reducing agent has a fixed carbon content greater than or equal to 80 wt %, and an ash content less than or equal to 10 wt %.
[0030] More preferably, the content of fixed carbon in the first carbonaceous reducing agent is 85 to 90 wt %.
[0031] More preferably, the ash content in the first carbonaceous reducing agent is 3-5 wt %.
[0032] The volatile content of the first carbonaceous reducing agent may be 3 to 15 wt %. In certain embodiments, the volatile content is 5 to 10 wt %.
[0033] The moisture content of the first carbonaceous reducing agent may be less than or equal to 5 wt %; preferably, the moisture content is 1 to 3 wt %.
[0034] The content of sulfur in the first carbonaceous reducing agent may be less than or equal to 1 wt %; preferably, the content of sulfur is less than or equal to 0.3 wt %.
[0035] More preferably, the content of fixed carbon in the second carbonaceous reducing agent is 85-90 wt %.
[0036] More preferably, the ash content in the second carbonaceous reducing agent is 3-5 wt %.
[0037] The volatile content of the second carbonaceous reducing agent may be 3 to 15 wt %. In certain embodiments, the volatile content is 5 to 10 wt %.
[0038] The moisture content of the second carbonaceous reducing agent may be less than or equal to 5 wt %; preferably, the moisture content is 1 to 3 wt %.
[0039] The content of sulfur in the second carbonaceous reducing agent may be less than or equal to 1 wt %; preferably, the content of sulfur is less than or equal to 0.3 wt %.
[0040] According to the treatment method of the present invention, preferably, the lanthanum slag contains La element, La2O3 and rare earth oxides;
[0041] The rare earth element in the rare earth oxide is selected from one or more rare earth elements other than lanthanum, the content of La single substance is 1-15wt%, the content of La2O3 is 75-97wt%, and the content of rare earth oxide is 1-10wt%.
[0042] More preferably, the content of La single substance is 3-6wt%, the content of La2O3 is 85-95wt%, and the content of rare earth oxide is 3-7wt%.
[0043] According to the treatment method of the present invention, preferably, the rare earth element in the rare earth oxide is selected from one or more of samarium, europium, ytterbium and thulium;
[0044] The lanthanum slag has a calcium content of less than or equal to 0.01 wt %, and a lithium content of less than or equal to 0.01 wt %.
[0045] The lanthanum slag of the present invention can be produced from the lanthanum slag produced by the lanthanum thermal reduction method to prepare metallic samarium, europium, ytterbium or thulium. Therefore, the lanthanum slag contains one or more of samarium oxide, europium oxide, ytterbium oxide and thulium oxide. In some embodiments, the rare earth oxide contained in the lanthanum slag is samarium oxide. In other embodiments, the rare earth oxide contained in the lanthanum slag is ytterbium oxide.
[0046] More preferably, the calcium content in the lanthanum slag is less than or equal to 0.005wt%, and the lithium content is less than or equal to 0.005wt%.
[0047] According to the treatment method of the present invention, preferably, the green body further contains a binder, and the binder is selected from one or more of water glass, microsilica powder, bentonite, pulp, syrup, and plant starch. More preferably, the binder is plant starch. The plant starch can be corn starch.
[0048] According to the treatment method of the present invention, preferably, the binder is used in the form of a colloid formed by mixing it with water.
[0049] In certain embodiments, the green body is comprised of lanthanum slag, a first carbonaceous reductant, a binder, and water.
[0050] The function of the colloid is to glue the lanthanum slag and the first carbonaceous reducing agent together to form a green body. The amount of the colloid can be determined as needed. In some embodiments, the amount of the colloid can be 0.5-8% of the total mass of the lanthanum slag and the first carbonaceous reducing agent; preferably 2-5%.
[0051] In some embodiments, the method further comprises the following steps: mixing lanthanum slag, a first carbonaceous reducing agent and a colloid to obtain a mixture, and pressing the mixture into a green body.
[0052] The content of SiO2 in the silica of the present invention is greater than or equal to 97wt%; preferably, the content of SiO2 is greater than or equal to 99wt%.
[0053] The amount of silica used can be determined based on the resulting rare earth ferrosilicon alloy.
[0054] In the treatment method of the present invention, step (2) can be operated continuously. This ensures continuous production. During continuous production, the material distribution can be adjusted according to the rate of discharge. During continuous production, an iron or steel tamping rod can be used to tamping the furnace every 6 to 8 hours.
[0055] The processing method according to the present invention preferably further comprises the following steps:
[0056] The flue gas generated during the smelting process is subjected to dust removal treatment and the dust in the flue gas is collected.
[0057] These dusts are silicon powder, which can be used to make cosmetics, high-purity silicon, etc.
[0058] In some embodiments, the alloy melt obtained by smelting can be left to stand, and the slag can be floated to the liquid surface before casting and forming. The standing time can be 5 to 30 minutes, preferably 10 to 20 minutes.
[0059] In certain embodiments, the method further comprises the step of separating and crushing the cast alloy ingot into blocks to obtain rare earth ferrosilicon alloy.
[0060] According to the treatment method of the present invention, preferably, the content of rare earth elements in the rare earth ferrosilicon alloy is 20-35wt%, and the total content of silicon and iron is 65-80wt%.
[0061] More preferably, the content of rare earth elements in the rare earth ferrosilicon alloy is 25-30 wt%, and the total content of silicon and iron is 70-75 wt%.
[0062] According to the treatment method of the present invention, preferably, the content of lanthanum in the rare earth ferrosilicon alloy is 17-32wt%, the content of silicon is 45-65wt%, and the content of iron is 12-30wt%.
[0063] More preferably, the content of lanthanum is 22-27 wt %, the content of silicon is 50-55 wt %, and the content of iron is 16-23 wt %.
[0064] In the rare earth ferrosilicon alloy, the content of the rare earth elements other than lanthanum may be 1 to 5 wt %, preferably 2 to 3.5 wt %.
[0065] The present invention can transform the solid waste lanthanum slag generated by the lanthanum thermal reduction method into valuable rare earth ferrosilicon alloy, turning waste into treasure, making full use of rare earth resources, greatly reducing the manufacturing cost of rare earth ferrosilicon alloy, and having extremely high commercial value. The rare earth ferrosilicon alloy obtained by the treatment method of the present invention has high purity and high rare earth recovery rate. DETAILED DESCRIPTION
[0066] The present invention is further described below in conjunction with specific embodiments, but the protection scope of the present invention is not limited thereto.
[0067] Here is the test method:
[0068] Chemical composition of lanthanum slag:
[0069] The lanthanum slag was ground and oxidized and roasted in air at 850°C for 2h. The weight gain of the product was weighed, which corresponded to the weight gain of metal lanthanum by oxidation. The weight of lanthanum in the lanthanum slag was calculated from the La2O3 molecular formula. The remaining components were measured by ICP analysis.
[0070] Chemical composition of blue carbon:
[0071] The test is carried out according to the method specified in GB / T 25211-2023 Classification and quality requirements of semi-coke products.
[0072] Chemical composition of rare earth ferrosilicon alloy:
[0073] The test was carried out according to the method specified in GB / T 4137-2024 Rare Earth Ferrosilicon Alloy.
[0074] Rare earth recovery rate: (total weight of rare earth in rare earth ferrosilicon alloy / total weight of rare earth in lanthanum slag)×100%.
[0075] Here are the raw materials:
[0076] The chemical composition of blue carbon is shown in the following table:
[0077] Fixed carbon content (wt%) Sulfur content (wt%) Ash content (wt%) Volatile content (wt%) Moisture content (wt%) 86.13 <0.3 4.02 7.64 1.91
[0078] The chemical composition of the lanthanum slag obtained by the lanthanum thermal reduction method to prepare samarium is shown in the following table:
[0079] <![CDATA[La2O3 content (wt%)]]> La content (wt%) <![CDATA[Sm2O3 content (wt%)]]> Ca content (wt%) Li content (wt%) 87.36 5.72 6.64 <0.005 <0.005
[0080] The chemical composition of the lanthanum slag obtained by the lanthanum thermal reduction method to prepare ytterbium is shown in the following table:
[0081] <![CDATA[La2O3 content (wt%)]]> La content (wt%) <![CDATA[Ytterbium oxide (Yb2O3) content (wt%)]]> Ca content (wt%) Li content (wt%) 92.52 3.24 4.23 <0.005 <0.005
[0082] Embodiment 1-2
[0083] Disperse industrial corn starch in water, heat and stir, and add water to dilute it into a colloid after the corn starch is gelatinized.
[0084] After mixing lanthanum slag with an average particle size of 20 mm and first blue carbon with an average particle size of 20 mm, the mixture is mixed with a colloid to obtain a mixture. The amount of the colloid is 3% of the total mass of the lanthanum slag and the first blue carbon. In terms of fixed carbon, the amount of the first blue carbon is 25wt% of the theoretical amount required to reduce the rare earth oxides in silica and the lanthanum slag. The mixture is pressed into a cylindrical body of φ200mm×200mm using an oil press. The body is pre-baked at 450°C for 60 minutes to obtain a pre-baked product.
[0085] The pre-baked product, the second blue coke with an average particle size of 20 mm and the silica with an average particle size of 110 mm are mixed to obtain a smelting raw material. The smelting raw material is distributed to the submerged arc furnace using a distribution machine, and smelted for 5 hours at a furnace bottom temperature of 1800° C. to obtain an alloy melt. In terms of fixed carbon, the amount of the second blue coke is 125wt% of the theoretical amount required to reduce the rare earth oxides in the silica and lanthanum slag. The flue gas generated during the smelting process is subjected to dust removal treatment, and the dust in the flue gas is collected.
[0086] The alloy melt is allowed to stand in the tundish for 15 minutes to allow the slag to float to the liquid surface, and then poured into an ingot mold and cooled to obtain an alloy ingot.
[0087] The alloy ingot is divided and crushed into blocks with an average particle size of 30 mm to obtain rare earth ferrosilicon alloy.
[0088] The source of lanthanum slag and rare earth recovery rate are shown in Table 1, and the element composition of rare earth ferrosilicon alloy is shown in Table 2.
[0089] Table 1
[0090] Source of lanthanum slag Rare earth recovery rate (wt%) Example 1 Lanthanum slag obtained by preparing samarium by lanthanum thermal reduction 93.3 Example 2 Lanthanum slag obtained by lanthanum thermal reduction method to prepare ytterbium 94.5
[0091] Table 2
[0092] TRE (wt%) La(wt%) Sm (wt%) Yb(wt%) Si (wt%) Fe(wt%) Example 1 27.36 24.65 2.71 — 52.31 20.33 Example 2 28.18 25.35 — 2.83 53.21 18.61
[0093] The present invention is not limited to the above-mentioned embodiments. Without departing from the essential content of the present invention, any deformation, improvement and substitution that can be conceived by those skilled in the art shall fall within the scope of the present invention.
Claims
1. A method for treating lanthanum slag, characterized in that: The steps include: (1) pre-baking a green body containing a first carbonaceous reducing agent and lanthanum slag at 400 to 600° C. for 50 to 120 minutes to obtain a pre-baked product; (2) smelting the smelting raw materials including the pre-baked product, the second carbonaceous reducing agent and silica at 1700-2200° C. for 3-8 hours to obtain an alloy melt; (3) casting the alloy melt to obtain rare earth ferrosilicon alloy; The first carbonaceous reducing agent is selected from one or more of coke, blue charcoal, semi-coke, charcoal, gas coke, bituminous coal, and petroleum coke; the amount of the first carbonaceous reducing agent is 20-30wt% of the theoretical amount of rare earth oxides contained in the reduced silica and lanthanum slag based on the fixed carbon contained in the first carbonaceous reducing agent; Wherein, the second carbonaceous reducing agent is selected from one or more of coke, blue coke, semi-coke, charcoal, gas coal coke, bituminous coal, and petroleum coke; based on the fixed carbon contained in the second carbonaceous reducing agent, the amount of the second carbonaceous reducing agent used is 100-180wt% of the theoretical amount of rare earth oxides contained in the reduced silica and lanthanum slag.
2. The processing method according to claim 1, characterized in that: The average particle size of the lanthanum slag is 5-30 mm, the average particle size of the first carbonaceous reducing agent is 5-30 mm, the average particle size of the second carbonaceous reducing agent is 5-30 mm, the average particle size of the silica is 40-150 mm, and the diameter of the smallest surrounding sphere of the blank is 100-300 mm.
3. The processing method according to claim 1, characterized in that: The first carbonaceous reducing agent has a fixed carbon content greater than or equal to 80 wt % and an ash content less than or equal to 10 wt %; The second carbonaceous reducing agent has a fixed carbon content greater than or equal to 80 wt %, and an ash content less than or equal to 10 wt %.
4. The processing method according to claim 1, characterized in that: The lanthanum slag contains La element, La2O3 and rare earth oxides; The rare earth element in the rare earth oxide is selected from one or more rare earth elements other than lanthanum, the content of La single substance is 1-15wt%, the content of La2O3 is 75-97wt%, and the content of rare earth oxide is 1-10wt%.
5. The processing method according to claim 4, characterized in that: The rare earth element in the rare earth oxide is selected from one or more of samarium, europium, ytterbium and thulium; The lanthanum slag has a calcium content of less than or equal to 0.01 wt %, and a lithium content of less than or equal to 0.01 wt %.
6. The processing method according to claim 1, characterized in that: The green body also contains a binder, which is selected from one or more of water glass, microsilica powder, bentonite, pulp, syrup, and plant starch.
7. The processing method according to claim 6, characterized in that: The binder is used in the form of a colloid formed by mixing it with water.
8. The processing method according to claim 1, characterized in that: The following steps are also included: The flue gas generated during the smelting process is subjected to dust removal treatment and the dust in the flue gas is collected.
9. The processing method according to claim 1, characterized in that: In the rare earth ferrosilicon alloy, the content of rare earth elements is 20-35wt%, and the total content of silicon elements and iron elements is 65-80wt%.
10. The processing method according to claim 1, characterized in that: In the rare earth ferrosilicon alloy, the content of lanthanum is 17-32wt%, the content of silicon is 45-65wt%, and the content of iron is 12-30wt%.
Citation Information
Patent Citations
Ceric rare earth ferrosilicon alloy and production method thereof
CN104878289A
Lanthanum based rare-earth (Mg) Si-Fe alloy and related smelting process
CN1061802A
Process for preparation of rareearth ferro-silicon alloy by carbon thermal reduction to ore bearing O,C and Ce
CN1071205A
Method for smelting and producing silicon alloy material by submerged arc furnace
CN116121582A
Method for producing rare earth ferrosilicon alloy by using rare earth slag
CN116426773A